Adjustment of children with with special needs in regular education classrooms - Pruna, Amelia C. (2006)
The study focused on the adjustment of children with special needs (CSN) who are integrated in the regular education classrooms. Seven CSN with different cases, 5 class advisers, 3 subject teachers, 7 parents of CSN, and 30 regular classmates of CSN comprised the subjects of the study. The following areas were examined in the study: perceptions of CSN about the school, modifications used by teachers, behaviors of CSN in different classroom situations, learning areas, and their physical preparedness, and perceptions of classmates, teachers, and parents. CSN were perceived to have been adjusted to the school environment and other people as well as with different classroom situations and learning areas. Parents believed their children showed progress in socialization and academic gains as a result of integration with regular children. Teachers modified instruction to accomodate learning needs of special children.
"March 2006."
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Children with disabilities -- Education -- Philippines -- Bataan; Adjustment (Psychology); Special education -- Philippines -- Bataan